Frictions and Fictions of Community: Structures and Representations of Power in Central Europe, c. 1350-1500. (October 2016) - Burkhardt, Julia
This article analyses structures and representations of power in late medieval Central Europe between 1350 and 1500. Using the examples of the medieval kingdoms of Poland, Bohemia, Hungary and Germany, the study describes and compares social structures and their political implementation, fora of political discourse, achievements in constitutional and theoretical writing as well as codification of laws and privileges. The focus on "community" as a key term in the political discourse allows shedding light on modes of distributing political powers, the reciprocity and interconnections of political players and the development of notions of political representation. Against this background, the article presents the formation of structures and representations of power in late medieval Central Europe as a highly dynamic process, revealing both fictions and frictions of community.